Effect of Neurexan on the pattern of EEG frequencies in rats - Dimpfel Wilfried; Roeska Kerstin; Seilheimer Bernd (BMC, 2012)
Abstract Background Various medications of natural origin have effectively treated stress-related disorders, such as sleep disturbances and agitated conditions. The efficacy of Neurexan, a multicomponent, low-dose medication, has been demonstrated in observational studies, but its exact mechanism of action has not been determined. Methods To characterize the effects of Neurexan on the central nervous system, we analyzed the spectral frequencies of field potentials in four rat brain areas after a single oral administration of Neurexan. Different doses of Neurexan were tested within a crossover design, and effects were compared with vehicle control. Results Significant effects were observed with 0.5 tablets of Neurexan, predominantly on δ- and θ-waves in the frontal cortex and reticular formation (P < 0.01). In the reticular formation, significant changes of δ- and θ-waves occurred as early as during the first hour after administration. The time course revealed a significant and longer-lasting increase of δ- and θ-waves in the frontal cortex and reticular formation, whereas other spectral frequencies were only transiently affected in the frontal cortex, reticular formation, and striatum. Conclusion In conclusion, this study demonstrated that the low-dose medication Neurexan influences central nervous system activity in rats. The resulting electroencephalographic profile of Neurexan shows several similarities with those of other calming agents, such as Valeriana and Passiflora, suggesting a potential benefit of Neurexan for patients with stress-related disorders. Moreover, this report demonstrates that electroencephalographic signatures are also valid biomarkers for the assessment of low-dose medications, such as Neurexan.